Mechanical Properties and Mesostructure Evolution of Fibre-Reinforced Loess under Freeze-Thaw Cycles - Longfei Zhang; Zaiqiang Hu; Hongru Li; Haicheng She; Xiaoliang Wang; Xiaoning Han; Xi Yang (Advances in Civil Engineering)
The strength of loess in seasonal frozen soil areas decreases evidently due to the freeze-thaw cycle, which even leads to some engineering and geological problems. Fibre reinforcement is very effective in improving the mechanical properties of soil. Triaxial tests under different water contents, freezing temperatures, and number of freeze-thaw cycles were carried out for fibre-reinforced loess to study the ability of fibre reinforcement to improve the resistance of loess to freeze-thaw damage; scanning electron microscopy (SEM) was also conducted. The effects of freeze and thaw deterioration and reinforcement were discussed by comparing the strength parameters under different test conditions, and the influence mechanism of freezing temperature, number of freeze-thaw cycles, and reinforcement on loess strength was explained. Results show that a lower freezing temperature indicates a more evident decrease in strength after thawing. Under the action of the first five freeze-thaw cycles, the degree of decrease is more prominent. The fibre reinforcement can reduce the fragmentation of aggregates in loess, thereby effectively restraining the deterioration effect of loess during freeze-thaw cycles. Finally, the strength parameter prediction model under different freeze-thaw cycles of reinforced loess is established, thereby providing theoretical support for engineering application and numerical simulation of fibre-reinforced loess.